Early history of glycine receptor biology in mammalian spinal cord circuits - Callister, Robert J.; Graham, Brett A. (Frontiers in Molecular Neuroscience, 2010)
In this review we provide an overview of key in vivo experiments, undertaken in the cat spinal cord in the 1950s and 1960s, and point out their contributions to our present understanding of glycine receptor (GlyR) function. Importantly, some of these discoveries were made well before an inhibitory receptor, or its agonist, was identified. These contributions include the universal acceptance of a chemical mode of synaptic transmission, that GlyRs are chloride channels, are involved in reciprocal and recurrent spinal inhibition, are selectively blocked by strychnine, and can be distinguished from the GABAA receptor by their insensitivity to bicuculline. The early in vivo work on inhibitory mechanisms in spinal neurons also contributed to several enduring principles on synaptic function, such as the time associated with synaptic delay, the extension of Dale’s hypothesis (regarding the chemical unity of nerve cells and their terminals) to neurons within the central nervous system, and the importance of inhibition for synaptic integration in motor and sensory circuits. We hope the work presented here will encourage those interested in GlyR biology and inhibitory mechanisms to seek out and read some of the “classic” articles that document the above discoveries.